VALUE-BASED ASSESSMENT AS AN ANALYTICAL LINGUISTIC CATEGORY: STRUCTURAL AND SEMANTIC FUNCTIONS IN THE LINGUISTIC WORLDVIEW - Salokhiddinov Manuchekhr (International Journal of Literature and Language Studies, 2026)
The present study offers a theoretical and scientific examination of axiological evaluation, framing it as a crucial category within linguistic analysis. It sheds light on the mechanisms underlying the formation of positive and negative evaluative meanings through various linguistic units, detailing their semantic, pragmatic, and cognitive characteristics. Additionally, the paper explores the contribution of value-based assessments to the construction of the linguistic worldview, highlighting their deep-rooted connections to national-cultural factors and their influence on the conceptual framework of language users. By analyzing concrete examples, the research investigates the manifestation of evaluative components across multiple linguistic tiers—specifically lexical, phraseological, and syntactic—and identifies their communicative and pragmatic roles. Ultimately, the findings substantiate the integral position of the axiological category within the language system and its vital function in shaping conceptual structures within the linguistic picture of the world.